Resolution of Thumb Pain following Adoption of Mathieu Needle Holder: An Ergonomic Analysis - Olga Schuth, MD; Jeremy Powers, MD; Wyndell Merritt, MD; Nadia Blanchet, MD (Plastic and Reconstructive Surgery, Global Open, 2020)
Background:. As surveys reveal the prevalence of musculoskeletal pain among surgeons, it is important to have an appreciation and understanding of surgical ergonomics to protect against long-term injuries and mitigate the symptoms of existing conditions. Surgeons diagnosed with thumb carpometacarpal (CMC) joint osteoarthritis, a progressive and debilitating condition, can be especially vulnerable to the pain caused by the repetitive manual tasks of operating.